Cover Image, Volume 38, Issue 8. Issue 8 (11th July 2017) - Dou, Yanmei; Yang, Xiaoxu; Li, Ziyi; Wang, Sheng; Zhang, Zheng; Ye, Adam Yongxin; Yan, Linlin; Yang, Changhong; Wu, Qixi; Li, Jiarui; Zhao, Boxun; Huang, August Yue; et al.
Abstract : On the cover : The cover image, by Yanmei Dou et al., is based on the Research Article Postzygotic single‐nucleotide mosaicisms contribute to the etiology of autism spectrum disorder and autistic traits and the origin of mutations, Pages 1002–1013. DOI 10.1002/humu.23284